Ketidakadilan Gender dalam Novel Namaku Matahari Karya Remy Sylado: Kajian Feminisme - Astuti, Sri; Abdurahman, Abdurahman; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2012)
The purpose of this study were (1) describe the forms of injustice gender in the novel Namaku Mata Hari by Remy Sylado, (2) describe the factors that cause gender inequality in the novel NamakuMata Hari by Remy Sylado. The data in this study is a sentence, paragraph or section that contains a novel about gender inequality in the work of the novel NamakuMata Hari by Remy Sylado, sources of data in this study is novel NamakuMata Hari by Remy Sylado works published by Scholastic Press PT. Techniques of data collection is done by stages; read carefully the novel NamakuMata Hari by Remy Sylado, identifying each part of the novel that support injustice gender form, classifying data, conduct library research, inventory data using the format of the data inventory. The findings of the study first is the forms of injustice gender in the novel NamakuMata Hari by Remy Sylado are: (1) the marginalization of women, (2) the subordination of women, (3) stereotypes of women, (4) violence against women, (5) double burden against women, and (6) discrimination against women. Second, the factors that cause gender inequality in the novel NamakuMata Hari by Remy Sylado are (1) factor of public confidence in the myth, (2) factors of rationality, (3) factors patriarchy and (4) factor of the capitalist system.